2018
DOI: 10.1001/jamainternmed.2018.3034
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sodium-Glucose Cotransporter 2 Inhibitors and Lower Extremity Amputation Among Patients With Type 2 Diabetes

Abstract: IMPORTANCE Results of clinical trials suggest that canagliflozin, a sodium-glucose cotransporter 2 (SGLT-2) inhibitor for treating type 2 diabetes, may be associated with lower extremity amputation. OBJECTIVE To quantify the association between the use of oral medication for type 2 diabetes and 5 outcomes (lower extremity amputation, peripheral arterial disease, critical limb ischemia, osteomyelitis, and ulcer). DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study was conducted using Truven Health Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
142
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 25 publications
6
142
2
2
Order By: Relevance
“…Second, we showed that canagliflozin‐only analyses yielded higher HR estimates versus DPP‐4 inhibitor and SU initiators, but lower HR estimates versus non‐metformin, non‐SGLT2 inhibitor initiators. This last result is more consistent with the canagliflozin‐specific HR estimates observed by Yuan et al and Ryan et al Third, analyses using ITT follow‐up typically yielded HR estimates closer to the null than those using as‐treated approaches, which may have contributed to the observed differences between Yuan et al and Ryan et al, versus Chang et al, Adimadhyam et al, and the present study. Fourth, our subgroup analyses showed that excluding patients with prior amputation and prior CKD reduced HR estimates, whereas excluding patients with baseline insulin use increased HR estimates.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Second, we showed that canagliflozin‐only analyses yielded higher HR estimates versus DPP‐4 inhibitor and SU initiators, but lower HR estimates versus non‐metformin, non‐SGLT2 inhibitor initiators. This last result is more consistent with the canagliflozin‐specific HR estimates observed by Yuan et al and Ryan et al Third, analyses using ITT follow‐up typically yielded HR estimates closer to the null than those using as‐treated approaches, which may have contributed to the observed differences between Yuan et al and Ryan et al, versus Chang et al, Adimadhyam et al, and the present study. Fourth, our subgroup analyses showed that excluding patients with prior amputation and prior CKD reduced HR estimates, whereas excluding patients with baseline insulin use increased HR estimates.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, which was planned and prespecified in 2017 prior to publication of other pharmaco‐epidemiological analyses, we observed a similarly elevated risk of LEA among SGLT2 inhibitor initiators versus DPP‐4 inhibitor comparators, and a similar null result versus initiators of all non‐metformin, non‐SGLT2 inhibitor GLDs (aHR 1.02, 95% CI 0.54‐1.93). However, results from the SU and non‐SGLT2 inhibitor comparisons were both substantively different from the results obtained by Chang et al, who made their comparisons against a suite of older GLDs including metformin, SUs and thiazolidinediones (aHR 2.12, 95% CI 1.19‐3.77). We attribute these differences to our simultaneous inclusion of insulin (typically a marker of more severe diabetes and higher amputation risk) and exclusion of metformin (often prescribed to patients with less severe diabetes and lower amputation risk) in the non‐SGLT2 inhibitor comparator group, which mirrors a commonly used comparator in previous studies …”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Evidence of cardio‐protection from SGLT2 inhibitors relative to other agents has led to a dramatic increase in use of these agents in recent years; thus, our findings are highly relevant as they identify another population‐based risk associated with use of SGLT2 inhibitors that should be carefully weighed against the benefits. While other reported risks associated with use of SGLT2 inhibitors are rare and severe, that is, euglycaemic ketoacidosis, lower limb amputations and acute kidney injury, genital mycotic infections are a common risk with use of SGLT2 inhibitors that affects both women and men.…”
Section: Discussionmentioning
confidence: 99%